Importance of Methods in Teaching (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
. In this article, opinions about the use of various methods and didactic methods in teaching mathematics to students of the Faculty of Humanities are discussed, as well as explained with examples.